Da produção colonial ao sistema agroindustrial : a modificação do perfil produtivo da região de Chapecó (1920-1980) - Serpa, Ivone Maria (2014)
This thesis aims to study the shift from production of small colonial property for agro-industrial production, with the formation of agricultural industries in the greater Chapecó in western Santa Catarina, between the years 1920-1980. This time frame is justified by the fact that 1920 is the beginning of the process of colonizing the companies operate, and 1980 marks the solidification process of the agroindustrial complex of the region. In methodological terms, we opted for the collection and analysis of a set of quantitative data, and literature review, which allowed monitoring the formation and development of agroindustrial production. The western region has been the subject of disputes over territory, given the diversity of possible activities to be practiced in the region. The colonizers were responsible for the process of attracting new residents, mostly settlers Grande River. Between 1920 and 1940 as well as being phase of colonization, has been the cycle of yerba mate, which then passes out of the activity of the wood, which meets the necessary clearance for the formation of villages, and the resulting profit arising from trade in the same, this cycle ends with the depletion of forests, giving way to agro cycle. The process of changing economic profile and production began with agricultural modernization, and drifted in the creation and expansion of agribusiness, between the 1970s and 1980s, from production systems integrated poultry and swine, which made the small family unit dependent and subordinated to the capitalist system of production. This process ensured, and assisted the development of the western region, making it a national benchmark regarding the agribusiness sector. The region has a colonial economy, between 1920 and 1940 to an economy based on agribusiness integration system initially pig, and later, of birds, between the years 1970 and 1980. Geared that way for large national and international market, becoming one of the largest agribusiness in the country